2023
DOI: 10.1097/rlu.0000000000004540
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 68Ga-FAPI PET/CT in Detection of Metastatic Lobular Breast Cancer

Abstract: PurposeInvasive lobular breast cancer (ILC) may be hard to detect using conventional imaging modalities and usually shows less avidity to 18F-FDG PET/CT. 68Ga–fibroblast activation protein inhibitor (FAPI) PET/CT has shown promising results in detecting non–18F-FDG–avid cancers. We aimed to assess the feasibility of detecting metastatic disease in patients with non–18F-FDG–avid ILC.MethodsThis prospective study included patients with metastatic ILC, infiltrative to soft tissues, which was not 18F-FDG avid. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The study cohort included patients with metastatic ILC, with non–FDG-avid PET/CT scans who had baseline 68 Ga-FAPI–avid PET/CT scans as described in a previous study, 4 and continued to undergo FAPI imaging as part of their clinical follow-up. Exclusion criteria included patients who refused or were noneligible for follow-up scans (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study cohort included patients with metastatic ILC, with non–FDG-avid PET/CT scans who had baseline 68 Ga-FAPI–avid PET/CT scans as described in a previous study, 4 and continued to undergo FAPI imaging as part of their clinical follow-up. Exclusion criteria included patients who refused or were noneligible for follow-up scans (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies show that 68 Ga-labeled fibroblast activation protein inhibitor ( 68 Ga-FAPI), a new PET/CT radiotracer targeting cancer-associated fibroblasts in the tumor microenvironment, can be used in disease detection, as many tumors depend on activated fibroblasts to sustain viability and growth 1–3 . This also includes invasive lobular breast cancer (ILC), which is difficult to detect and follow on CT or FDG PET/CT because of an infiltrative spread pattern and low avidity to FDG 4–7 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, [ 18 F]AlF-FAPI-74 was reported to have lower specificity activity when compared to its 68 Ga-labeled counterpart, which could potentially affect image quality [34]. Novel tracers have also been developed for single photon emission computed tomography (SPECT) imaging such as 99m Tc-labeled FAPI-34, 99m Tc-labeled FAP-targeting ligand (FL-L3), and 111 In-labeled QCP02. In addition to 177 Lu, FAPI molecules have also been radiolabeled with 188 Re, 90 Y, and 225 Ac for therapeutic application [35][36][37][38][39].…”
Section: Development Of Fap-targeting Radiopharmaceuticalsmentioning
confidence: 99%
“…Subsequently, a series of studies demonstrated that the TBR derived from 68 Ga‐FAPI PET can classify pathological response correctly after neoadjuvant chemotherapy for breast cancer [97, 98]. In addition, FAPI PET/CT could possibly be used for disease response assessment and follow‐up based on the strong correlation between cancer progression and regression and FAPI‐based tumor volume [99, 100].…”
Section: Clinical Applications Of Fap‐targeted Molecular Imaging In O...mentioning
confidence: 99%